Penggunaan Vie Structure untuk Praktik Nominee dalam Praktik Penanaman Modal di Indonesia - Reditha Saras, Anak Agung Ayu (UNES Law Review, 2023)
Indonesia is a popular place for foreign investors to carry out investment activities. The government as the host state can also then provide and determine restrictions to certain actions regarding this investment, among others by issuing Law Number 25 of 2007 concerning Investment and Government Regulations in Lieu of Law Number 2 of 2022 concerning Job Creation. The existence of these restrictions and prohibitions then causes certain parties to smuggle the law in order to make investment easier, including the practice of nominees. What will be discussed in this article is the validity of the nominee practice by looking at the VIE structure practice in the People's Republic of China and looking at it from a civil and corporate perspective. This research method uses normative legal research. The research results show that VIE Structure is a nominee practice which is prohibited in Indonesia. In addition, all agreements for nominee practice will be null and void by law.